1976
DOI: 10.1007/bf00582878
|View full text |Cite
|
Sign up to set email alerts
|

The product of theade1 gene inSchizosaccharomyces pombe: A bifunctional enzyme catalysing two distinct steps in purine biosynthesis

Abstract: The assignment of the known ade genes to steps in purine biosynthesis in Schizosaccharomyces pombe has been completed with the demonstration that an ade3 mutants lacks FGAR amidotransferase, ade1A mutants lack GAR synthetase and ade1B mutants lack AIR synthetase. A comparison of enzyme activity with map position for ade1 mutants shows that (1) complementing ade1A mutants lack GAR synthetase but posses wild type amounts of AIR synthetase, (2) complementing ade1B mutants lack AIR synthetase but posses variable a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“…Early complementation studies using mutants of yeast deficient in purine biosynthesis in Schizosaccharomyces pombe (Fluri et al, 1976) and Saccharomyces cerevisiae (Gross & Woods, 1971) suggested that GAR synthetase and AIR synthetase activities might reside on a single bifunctional polypeptide. In fact, biochemical studies by Fluri et al in 1976 indicated that these two activities copurified =100-fold from S. pombe and suggested that both activities were confined to a polypeptide of Mr 40 000. Interestingly, GAR synthetase was active both as a monomer (Mr 40000) and in multimeric forms (Mr 160000-240000), while AIR synthetase activity could only be associated with the multimeric forms.…”
Section: Discussionmentioning
confidence: 99%
“…Early complementation studies using mutants of yeast deficient in purine biosynthesis in Schizosaccharomyces pombe (Fluri et al, 1976) and Saccharomyces cerevisiae (Gross & Woods, 1971) suggested that GAR synthetase and AIR synthetase activities might reside on a single bifunctional polypeptide. In fact, biochemical studies by Fluri et al in 1976 indicated that these two activities copurified =100-fold from S. pombe and suggested that both activities were confined to a polypeptide of Mr 40 000. Interestingly, GAR synthetase was active both as a monomer (Mr 40000) and in multimeric forms (Mr 160000-240000), while AIR synthetase activity could only be associated with the multimeric forms.…”
Section: Discussionmentioning
confidence: 99%
“…GARS and AIRS are encoded at the same complex locus in yeasts but at a position separate from GART (26)(27)(28). The human Gart locus has been hypothesized to lie on human chromosome 14 based on complementation of the hamster Ade-E mutation by human chromosome 14 (29), whereas the loci for GARS and AIRS have been assigned to chromosome 21 (30,31), most likely in the q22 region of the chromosome (32).…”
Section: Discussionmentioning
confidence: 99%
“…First, these have both been well-characterized biochemically (9,10). Second, coordinate regulation ofthese genes has been found for the corresponding genes in Schizosaccharomyces pombe (11). Third, we possessed a number of mutants of each complementation group.…”
mentioning
confidence: 98%
“…The following 23 isozymes and 1 nutritional marker were assayed in the hybrid clones by using methods as described (19). Numbers in brackets correspond to human chromosome assignments (20): 6-phosphogluconate dehydrogenase [1]; malate dehydrogenase, soluble [2]; 1-galactosidase [3]; phosphoglucomutase 2 [4]; arylsulfatase B [5]; superoxide dismutase, mitochondrial [6]; f-glucuronidase [7]; glutathione reductase [8]; adenylate kinase [9]; proline requirement [10]; lactate dehydrogenase A [11]; lactate dehydrogenase B [12]; esterase D [13]; nucleoside phosphorylase [14]; hexosaminidase-A and pyruvate kinase [15]; phosphogluconate phosphatase [16]; galactokinase [17]; peptidase A [18]; glucose phosphate isomerase [19]; adenosine deaminase [20]; superoxide dismutase, soluble [21]; arylsulfatase-A [22]; and glucose-6-phosphate dehydrogenase [X].…”
mentioning
confidence: 99%